Adaptive disturbance observer-based improved super-twisting sliding mode control for electromagnetic direct-drive pump. (1st January 2023) - Lu, Yingtao; Tan, Cao; Ge, Wenqing; Zhao, Yanjun; Wang, Geng
Abstract: In this study, to enhance the frequency-flow characteristics of the novel electromagnetic direct-drive pump (EDDP). An adaptive disturbance observer-based improved super-twisting sliding mode control (ISTSMC-ADOB) is proposed to address the problem in which the response quality is deteriorated by factors such as parameter mismatch and disturbance. An adaptive disturbance observer (ADOB) is designed to achieve adaptive compensation, avoid the use of high-gain feedback, and extend the applicability of the conventional disturbance observer. An improved super-twisting sliding mode control (ISTSMC) based on the fast terminal sliding mode algorithm is designed to ensure faster convergence of the error in finite time. By combining the ADOB with the ISTSMC, the conservative parameter selection of the sliding mode control (SMC) is avoided, and the accuracy and robustness are further strengthened. The stability is analyzed based on Lyapunov. The results show that the proposed method effectively improves the steady-state accuracy, response speed, and robustness in trajectory tracking of the electromagnetic linear actuator for the EDDP. This further enhances the frequency-flow characteristics of the system.